Study on Mesoscale Damage Evolution Characteristics of Irregular Sandstone Particles Based on Digital Images and Fractal Theory - Lujing Zheng; Lulin Zheng; Yujun Zuo; Hao Liu; Bin Chen; Zhonghu Wu; Wenjibin Sun; Yingle Wang (Advances in Materials Science and Engineering)
To study the mesoscale damage evolution law of irregular sandstone particles, based on RFPA2D and digital image processing technology, a real mesostructure numerical model of irregular sandstone particles is established to simulate the breakage process of particles, the effects of loading conditions and mesoscale heterogeneity on irregular sandstone particle damage are studied, and the calculation method of fractal dimension of irregular rock particles mesoscale fracture is proposed. The results show that the fracture damage degree (ω) and fractal dimension (D) maximum values of the constrained particles are 0.733 and 1.466, respectively, and the unconstrained particles are 0.577 and 1.153, respectively. The final failure mode of constrained particles is more complicated than unconstrained particles, the damage is more serious, and the fracture is more complete. Thus, the larger values of D yield a more complicated final failure mode of the particles. Consequently, with the larger ω, the final damage is more serious, and the breakage effect is comparatively better. The study is of great significance for exploring the laws of rock particle breakage and energy consumption, rock breakage mechanism, and searching for efficient and energy-saving rock-breaking methods.